KRUMIROGA: LITERARY REVIEW - Chougule, Pragati Y.; Jadhav, Sujata P. (International Journal of Research -GRANTHAALAYAH, 2017)
Krumi is an important disease described in ayurvedic science and is described in detail with respect to its etiology, clinical features and treatment. The term krumi is used to denote tiny organisms which reside in human body. Concept of krumi and their relation in the development of disease is described in almost all ayurvedicsamhita. Acharyas also describe krumi as an etiological factor in various diseases. Krumi contribute significantly to global burden of diseases. Overcrowding, contamination of water, poor sanitation greatly favour transmission of parasitic infection resulting in high endemicity. Intestinal worm infestation results in impaired nutrition. Many neglect this condition as most of the times it may be asymptomatic. It maybe associated with malnutrition, iron deficiency anaemia, repeated gastrointestinal disturbances and upper respiratory tract infections.